Considerations On Dositej Obradović’s Stay And Travels In Italy - Lazarević Di Giacomo, Persida (Slavica Lodziensia, 2017)
This paper presents new data related to Dositej Obradović’s stay in Italy and the travels he undertook while he was there. In the period between 1769 and 1780 Obradović visited Trieste, Venice, Padua, Ferrara, Bologna, Florence, Pistoia, Lucca, Pisa, Livorno and Messina and later described these travels in his autobiography The Life and Adventures (1783). Although he is rather sketchy in his descriptions, we nonetheless discover that he became acquainted with a number of interesting fi gures of the day and was witness to contemporary events and phenomena: he tells us, for example, about the provveditore with whom he sailed to Venice and about the Rules of Health promulgated by the Venetian Republic in connection with the plague which was then raging. He also testifi es to the diet of the Venetian navy and the order issued by Catholic authorities prohibiting Orthodox priests from other countries from performing services in Dalmatia. The canale navile, in Bologna was also the object of Obradović’s attention. This artifi cial hydraulic system was a navigable channel making it possible to sail from Venice to Bologna(!) in the past. His descriptions of the heavily travelled road between Bologna and Florence and of the earthquake in Messina which took place after his departure for Chios are also interesting historical accounts of the period.